High LDL levels lead to increased synovial inflammation and accelerated ectopic bone formation during experimental osteoarthritis. Issue 5 (May 2016) - de Munter, W.; van den Bosch, M.H.; Slöetjes, A.W.; Croce, K.J.; Vogl, T.; Roth, J.; Koenders, M.I.; van de Loo, F.A.; van den Berg, W.B.; van der Kraan, P.M.; van Lent, P.L.
Summary: Objective: A relation between osteoarthritis (OA) and increased cholesterol levels is apparent. In the present study we investigate OA pathology in apolipoprotein E (ApoE) − /− mice with and without a cholesterol-rich diet, a model for high systemic low density lipoprotein (LDL) cholesterol levels independent of weight. Method: Wild type (WT), Apoe − /−, S100a9 −/− and Apoe − /− S100a9 −/− mice (C57BL/6 background) received a standard or cholesterol-rich diet. Experimental OA was induced by intra-articular injection of collagenase and animals were sacrificed at day 10 and day 36. Results: Although minimal differences in cartilage damage were found between the WT and ApoE − /− mice, increased synovial thickening was found in the latter. Thirty-six days after OA-induction, ApoE − /− mice on a standard diet showed increased ectopic bone formation, particularly at the medial collateral ligament, compared with OA in WT mice. Furthermore, a significant increase in synovial gene expression of both S100a8 and S100a9 and S100A8/S100A9 protein levels was found in ApoE − /− mice, suggesting an activated inflammatory status of synovial cells. In both ApoE − /− and WT mice, addition of a cholesterol-rich diet resulted in excessive bone formation in the medial collateral ligament at late-time-point OA. Interestingly, at the early time point, proteoglycan deposition was already significantly increased in ApoE − /− mice compared with WT mice. Mice deficient for both ApoE and S100a9 also showed increased ectopic bone formation, but not synovial activation, suggesting a role for S100-proteins in cholesterol-mediated synovial activation. Conclusions: Increased cholesterol levels strongly elevate synovial activation and ectopic bone formation in early-stage collagenase-induced OA.